Efectos del incremento de fosfatos en un sistema experimental, usando biomasa del perifiton y macroinvertebrados acuáticos como indicadores - Mariño Castro, Olger Jair (2019)
The eutrophication process is linked to the nutrient load that is often associated with anthropogenic activities. Phosphorus limits the growth of algae, which results in low productivity. In Ecuador, no experimental studies on the effects of phosphorus pollution on Andean aquatic ecosystems at different concentrations have been developed. The objective of this research was to evaluate the relationship between the change in periphery biomass and the impact on the life cycle of aquatic macroinvertebrates (Nectopsyche sp.), Using different phosphate concentrations. For this study, a microcosm experiment was designed using four treatments based on phosphorus concentrations related to agricultural-livestock use and urban land use of the Guayllabamba river basin. The maximum allowable value was also considered according to the Ecuadorian Regulations. The process of colonization of algae in biofilm began 14 days before the experiment, to ensure the presence of peripheron in each treatment. The results indicated an increase in biomass due to phosphate enrichment. There was a greater accumulation of primary producers, and a sharp decrease in components of organic matter, because the system changed to be slightly autotrophic. The conductivity increased both in time and in the different treatments by evaporation of water in microcosm. With respect to the sublethal variables such as the head width or the weight of the individuals, there was an increase in all treatments. The width being statistically significant in treatments of 1 and 10 mg / L. The mortality rates of the individuals were higher in the treatment of 20 mg / L where it registered 35% of dead organisms in the total population. In conclusion, as phosphate concentrations increase in contaminated rivers, the survival rate of Nectopsyche is negatively affected. This could be due to the changes in conductivity that affect the processes of osmoregulation and atrophy of the respiratory organs.